Identification of Medicinal Plants in the Ciudad Universitaria (Madrid): new data from microscopic observations - Peyrat, Laure-Anne; Trawinska, Monika J.; Gavilán, Rosario G. (Lazaroa, 2012)
A study of medicinal flora is currently under way at the Ciudad Universitaria (Madrid), based on a previous study of flora in which 416 plants were compiled. We have selected plants with a therapeutic use collected in the study area which have been identified both macroscopically and microscopically using the appropriate tools. This paper presents a complete description of eleven taxa.